Economic Impact of the 11th Douro Valley Half Marathon - Carvalho Maria José; Sousa Marisa; Paipe Gustavo; Bavaresco Gustavo; Felipe José Luis (Sciendo, 2018)
The aim of this study was to analyze the direct economic impact of the 11th Douro Valley Half Marathon held in Portugal in 2016. An ad-hoc questionnaire was designed for collecting data. It was composed of four dimensions: (i) socio-demographic data, (ii) expenses, (iii) sports practice, and (iv) satisfaction with the event (54 items in total). There were 375 questionnaires randomly collected in a total of 16,330 runners. The mean expense of local participants in this half marathon was €219, while non-resident participants expended about €320. Thus, the local participants' inflow was €1,036,965, while the non-resident participants' inflow was €3,709,760, resulting in a total participant inflow of €4,746,725. Regarding the participants' specific expenses, the following order was obtained: 1st, accommodation; 2nd, food; 3rd, travel costs; 4th, shopping. It was calculated that the total local economic impact of the 11th Douro Valley Half Marathon participants was almost five million euros (€4,746,725).